GIS and decision support systems for malaysian development plan studies - Yaakup, Ahris; Johar, Foziah; Maidin, Mohd. Anuar; Ahmad, Ezrein Faizal (2004)
The Malaysian development planning system was refined in line with the amendment of the Town and Country Planning Act, 1976 (Act 172) in year 2001. The amended Act plays a major role in the reform of the development planning system in the sense that it insists the incorporation of the Geographical Information System (GIS) into the development plan preparation process at all planning hierarchy, be it the macro or micro level. Apparently, the preparation of development plans calls for a continuous and cyclical planning process comprising the identification of needs and goals, formulation and evaluation of alternatives as well as monitoring the implementation of the plans. GIS is claimed to be an effective tool in providing analytical and quantitative methods for urban and regional planning analysis, and thus offer a strong platform for decision-making in its role as the major component of Decision Support Systems (DSS). Currently, the adoption of Multi Criteria Decision-Making (MCDM) technique and use of DSS such as What if?, Definite and ILWIS while utilising the GIS spatial analysis capabilities have been among the new approach in the formulation of the spatial development strategies. This paper will focus on the application of GIS for the development plan formulation and implementation at both the state (macro) and district (micro) levels based on case studies of the Pahang State Structure Plan, Application of GIS for Klang Valley (AGISwlk) and the Pekan District Local Plan. Beginning from the philosophy and conceptual aspects of the application of GIS for development planning, this paper will briefly discuss the preparation of GIS for the purpose of the development plans formulation and implementation. This paper will also emphasize on the application of the MCDM technique in the formulation of strategies and policies at the state level through generation of development scenario alternatives, as well as location-allocation at the district level. Finally, the paper discusses the challenges and prospects of GIS/DSS for development plan studies.